STAR: A Multimedia Database System for Trademark Registration - NARASIMHALU, Arcot Desai (Institutional Knowledge at Singapore Management University, 1994)
To ensure the uniqueness of all trademarks registered is very important. With ever increasing number of registered trademarks, this is becoming increasingly difficult. A system for search and registration of trademarks is presented in this paper. Trademarks are complex patterns consisting of various image and text patterns, called devicemark and word-in-mark respectively. Traditionally, only text part has been used for search and retrieval of such patterns. This was largely due to the diversity and complexity of image patterns occurring in trademarks. The System for Trademark Archival and Registration (STAR) presented here, uses features based on image as well as text components of trademarks and brings out the conflicting trademarks for the consideration of trademark officer. Thus, it simplifies the task of trademark office to a great extent. A structural representation consisting of image, graphics, text, and phonetics has been proposed to handle the diversity and complexity of trademarks. Based on this structural representation, an object-oriented database schema, a sophisticated segmentation technique, a composite similarity measure for searching conflicting trademarks, and an indexing scheme have been developed. Initial results are very promising. More testing is in progress.